2017
DOI: 10.1002/dta.2341
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of doping biomarkers after administration of a single dose testosterone gel

Abstract: Micro-doping with testosterone (T) is challenging to detect with the current doping tests. Today, the methods available to detect T are longitudinally monitoring of urine biomarkers in the Athlete Biological Passport (ABP) and measuring the isotopic composition of excreted biomarkers to distinguish the origin of the molecule. In this study, we investigated the detectability of a single dose of 100 mg T gel in 8 healthy male subjects. We also studied which biomarkers were most sensitive to T gel administration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 38 publications
(81 reference statements)
5
54
1
Order By: Relevance
“…Since urinary E is an important biomarker in the ABP, being the denominator in two of the five ratios used today, it is important to understand how E excretion varies in different settings when interpreting fluctuations in the ABP. Here we show that T/E and 5αAdiol/E ratios (the same two ratios that increase after testosterone administration in males) were increased by HCs, and for some participants the increase was very pronounced The individual cut‐off ranges calculated by the ABP software after four baseline values in our previous study show that changes in T/E between 200 and 400% can result in atypical findings in females . Here some individuals showed 4‐fold or even higher increases of T/E and 5αAdiol/E after HC use, which would likely cause atypical findings if the baseline values were collected when not on HC treatment.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Since urinary E is an important biomarker in the ABP, being the denominator in two of the five ratios used today, it is important to understand how E excretion varies in different settings when interpreting fluctuations in the ABP. Here we show that T/E and 5αAdiol/E ratios (the same two ratios that increase after testosterone administration in males) were increased by HCs, and for some participants the increase was very pronounced The individual cut‐off ranges calculated by the ABP software after four baseline values in our previous study show that changes in T/E between 200 and 400% can result in atypical findings in females . Here some individuals showed 4‐fold or even higher increases of T/E and 5αAdiol/E after HC use, which would likely cause atypical findings if the baseline values were collected when not on HC treatment.…”
Section: Discussionmentioning
confidence: 53%
“…The ratios monitored are T/E, A/Etio, 5αAdiol/E, 5αAdiol/5βAdiol, and A/T. It has been shown that the use of ABP increases the sensitivity of detecting the administration of testosterone in men …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Future MS approaches may also include other peptide and proteins with growth-promoting properties. 25,26 An additional endocrine module including IGF-I and P-III-NP would most likely also increase the sensitivity for recGH detection. This has improved the sensitivity to detect administration of low doses of testosterone.…”
Section: Hours and 3 Hours) After An Injection This Results Is In Agrmentioning
confidence: 99%
“…It is possible that longitudinal monitoring of the ABP biomarkers in our participants rather than single urine sampling would have resulted in atypical findings. It has been shown that the implementation of ABP has increased the probability of detecting testosterone gel use in men . It is known that basal T/E ratios are higher in men than in women and that the administration of intramuscular testosterone enanthate affects the T/E ratio to a larger degree in men than in women …”
Section: Discussionmentioning
confidence: 99%